Indian Nationalism and the Early Congress - McLane, John R., 1935- (Book collections on Project MUSE., 1977)
Tracing the history of the Indian National Congress from its founding in 1885 until about 1905, Professor McLane analyzes its efforts to build a national community and to obtain fundamental reforms from the British. In so doing, he extends our understanding of the dynamics of Indian pluralism. In its first two decades of existence, the Congress failed to inspire sacrifices from its members or to attract Muslims or Indians without an English education. The author explains this early stagnation in terms of developments within the Congress as well as outside in Indian society.Originally published in 1978.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.